KONSEP AGAMA DALAM KEHIDUPAN MASYARAKAT JEPANG - Mulyadi, Budi (IZUMI, 2017)
This research entitled The Religion Concept in The Life of Japanese Cociety. The main goal of this reserach is to know about The Religion Concept in The Life of Japanese Cociety. This research is combination between field and liblary reserach. Main method are observation, interview, interpretation. The research show Shinto and Buddhism are the main religion in Japan. The Japanese society has unique the life of religion which diferent compared with many other country. For Japanese people religion is not important things. Religion is thougt as one of culture product so can be amended as they like. They mix one religion with the other religion in ritual or religion ceremony.  gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor